Binder jet 3D printing of H13 tool steel for applications in injection moulding - Woo, Justin Kai Jie (Nanyang Technological University, 2024)
The modern manufacturing landscape increasingly relies on Additive Manufacturing (AM) technologies to meet the demands for complex, high-performance components. This study focuses on optimising the Binder Jet 3D Printing (BJ3DP) process to produce porous H13 Tool Steel parts suitable for injection moulding applications, aiming to bridge the gap between AM capabilities and tooling requirements in the industry.